Pengaruh Tingkat Partisipasi Angkatan Kerja dan Penanaman Modal Asing Terhadap Produktivitas Tenaga Kerja Sektor Jasa ASEAN-5 - Nurdiya Khairani Awwaliyyah (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
The service sector has an increasingly strategic role in encouraging economic growth in the ASEAN region, so that labor productivity is an important indicator in assessing economic performance and competitiveness. However, differences in participation and foreign investment flows still affect productivity achievements between countries. This study aims to examine the effect of Labor Force Participation Rate (LFPR) and Foreign Direct Investment (FDI) on labor productivity in the service sector in ASEAN-5 countries (Indonesia, Malaysia, Philippines, Singapore, and Thailand) during the period 2000–2023. Secondary data collected from the World Bank are analyzed using a panel data regression approach based on the Fixed Effect Model (FEM). The regression analysis demonstrates that both LFPR and FDI positively and significantly influence labor productivity in the service sector both partially and simultaneously. The results reveal that the increase in labor force participation reflects a more optimal utilization of the productive age workforce, while FDI contributes through capital flows, technology transfer, and improvement of managerial practices channeled through labor. Thus, the study reveals that reinforcing employment policies and enhancing the quality of foreign investment are key drivers of service sector productivity in the ASEAN-5 region.